2019
DOI: 10.1371/journal.pone.0213368
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of forestation and deforestation on local temperature across the globe

Abstract: Changing forest cover is a key driver of local climate change worldwide, as it affects both albedo and evapotranspiration (ET). Deforestation and forestation are predicted to have opposing influences on surface albedo and ET rates, and thus impact local surface temperatures differently. Relationships between forest change, albedo, ET, and local temperatures may further vary regionally, as the strengths of warming by albedo effects and cooling by ET effects vary with latitude. Despite these important relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 47 publications
5
60
0
4
Order By: Relevance
“…A variety of satellite-based datasets describing forest cover and climate variables as well as their changes have been developed and applied in site-based pairs and individual time-based statistical modeling methods [15,16]. Forest change can significantly affect surface temperature, and the area, magnitude, and direction of any changes vary significantly from local to global scales [7,17,18]. Some studies have found the inconsistent warming or cooling effects of forest change on temperature [7,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of satellite-based datasets describing forest cover and climate variables as well as their changes have been developed and applied in site-based pairs and individual time-based statistical modeling methods [15,16]. Forest change can significantly affect surface temperature, and the area, magnitude, and direction of any changes vary significantly from local to global scales [7,17,18]. Some studies have found the inconsistent warming or cooling effects of forest change on temperature [7,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been refined in order to quantify the potential effects of the hypothetical land use change (i.e., no change between land cover types) and the effects of the actual change (i.e., land cover change minus local no-change in two time periods) on surface temperature [15]. Sampling scales for the change estimation, such as moving window size, circle area, or even larger sizes, have been utilized [18,24,26]. In actuality, the conversion from forest to other types between different years would have different impacts on both the sign and magnitude of the surface temperature [17,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Amazon rainforest plays a pivotal role in regulating Earth's climate (Bonan 2008, Malhi et al 2008. In this sense, Amazon deforestation leads to regional and global average temperature rise (Baker & Spracklen 2019, Cohn et al 2019, Prevedello et al 2019, and changes in the Amazon biome are associated with an increase in the frequency of extreme weather events, such as droughts, altered rain patterns, heat waves, cold waves, and severe storms (Nepstad et al 2008, Sena et al 2014, Wu et al 2016, Stoy 2018, Leite-Filho et al 2019. Deforestation also facilitates forest fires, since degraded areas are naturally more susceptible to combustion.…”
Section: Problems and Activities Associated With Amazon Deforestationmentioning
confidence: 99%
“…In addition to reducing deforestation, it is necessary to recuperate degraded areas. Reforestation, afforestation, and restoration of forest environments help mitigate climate change through carbon sequestration, and social, ecological and economic benefits are obtained through the recovery of degraded forest areas (Bonan 2008, Brancalion et al 2019, Bustamante et al 2019, Prevedello et al 2019. However, the carbon and biodiversity benefits of preventing Amazonian deforestation are much greater than those of forest recovery, both per hectare and per unit cost, making avoiding deforestation the current priority in the Amazon region (Fearnside 2017b).…”
Section: How To Mitigate the Impacts Of Deforestationmentioning
confidence: 99%